Pendinginan Pengelasan menggunakan Metode SMAW pada Kekerasan Baja Karbon ST3 dengan Media Serbuk Semen Putih dan Beban Rockwell 100kgf - Muh Anhar; Asep Ruchiyat (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2020)
Welding is an inseparable part of the growth of industrial improvements because it plays a leading role in the engineering and repair of metal production.This study aims to determine the effect of cooling media on the hardness of weld metal and HAZ (heat Affected Zone) which tested hardness using the Rockwell method. This research was conducted on ST 37 low carbon steel material which was welded using 2.6 mm diameter E6013 electrode with blunt connection, then cooled using white cement powder.Welding metal cooled with white cement powder media has a harder hardness, because white cement contains C2S which is difficult to hydrate and does not have heat properties. After testing at several points, the result is an average value of raw material specimens is 48, 3 HRB, welding without isolator media = 42.96 HRB and HAZ = 46.4 HRB. Specimens using white cement powder = 47.65 HRB and HAZ = 48.2 HRB. Seen from this phenomenon and white cement has a hardness value lower than air, where the HAZ at the air value hardness was 46.4 HRB and the value of the white cement was higher at 48.2 HRB.